2021
DOI: 10.1155/2021/6646269
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and Physicochemical Quality of Drinking Water in Wegeda Town, Northwest Ethiopia

Abstract: Waterborne diseases continue to challenge communities in low-income countries like Ethiopia. Clinical information in Wegeda town showed that the prevalence of waterborne diseases was 58%. This study aimed to evaluate bacteriological and physicochemical drinking water quality in Wegeda town. This study will add valuable scientific data for future intervention. Water samples from protected and unprotected springs, hand-dug well, taps, and households’ containers were collected from November 2018 to June 2019 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
(16 reference statements)
4
15
0
Order By: Relevance
“…According to Li and Liu (2019), coliforms have got the capability of producing acid and gas when subjected to incubation at the temperatures adopted in this current study. Again, the results obtained in this study on the ability of coliforms to produce gas and acid when found in any water sample are in agreement with other reports that detected total and faecal coliforms in the assayed water samples in their respective study areas (Adeleye et al, 2020;Amoo et al, 2021;Baye Sitotaw et al, 2021). However, the bacterial isolates did test positive to methyl red, glucose, mannitol catalase, indole and lactose but tested negative to urease, oxidation fermentation, triple sugar iron, citrate, gelatin, nitrate reduction and voges-proskauer confirming that Escherichia coli existed in the assayed water samples.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to Li and Liu (2019), coliforms have got the capability of producing acid and gas when subjected to incubation at the temperatures adopted in this current study. Again, the results obtained in this study on the ability of coliforms to produce gas and acid when found in any water sample are in agreement with other reports that detected total and faecal coliforms in the assayed water samples in their respective study areas (Adeleye et al, 2020;Amoo et al, 2021;Baye Sitotaw et al, 2021). However, the bacterial isolates did test positive to methyl red, glucose, mannitol catalase, indole and lactose but tested negative to urease, oxidation fermentation, triple sugar iron, citrate, gelatin, nitrate reduction and voges-proskauer confirming that Escherichia coli existed in the assayed water samples.…”
Section: Resultssupporting
confidence: 92%
“…However, the bacterial isolates did test positive to methyl red, glucose, mannitol catalase, indole and lactose but tested negative to urease, oxidation fermentation, triple sugar iron, citrate, gelatin, nitrate reduction and voges-proskauer confirming that Escherichia coli existed in the assayed water samples. The detection of Escherichia coli in all the water samples assayed in this study is a clear indication of recent feacal pollution of the boreholes (Odonkor and Ampofo, 2013;Miner et al, 2016;Baye Sitotaw et al, 2021).…”
Section: Resultsmentioning
confidence: 59%
“…Overall, the results showed that 58 which suggest agricultural activities could likely be the most significant contributor of nutrients in surface water. Similar findings (Daramola et al, 2021;Ighalo and Adeniyi, 2020;Joshua, 2021a;Sitotaw et al, 2021) also highlighted surface water contamination from agricultural activities including disposal of waste and sewage, industrial waste, and leachate from waste disposal sites. Generally, the results suggest that both water sources were unsafe for consumption and can likely result in health issues particularly to children, the elderly, and visitors.…”
Section: Results and Discussion Presenting Water Quality Parameterssupporting
confidence: 59%
“…indicate bacteriological contamination above stipulated guidelines which can result in waterborne or water-related diseases such as cholera, typhoid, diarrhea, and dysentery (Sitotaw et al, 2021). These are common diseases that are currently ravaging the nation's rural populace of which the case study area is not an exception.…”
Section: Ojimma Et Al Fjsmentioning
confidence: 99%
See 1 more Smart Citation